2022
DOI: 10.3389/fnmol.2022.1014251
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitophagy in the neurodegenerative diseases and its pharmacological advances: A review

Abstract: Neurodegenerative diseases are a class of incurable and debilitating diseases characterized by progressive degeneration and death of cells in the central nervous system. They have multiple underlying mechanisms; however, they all share common degenerative features, such as mitochondrial dysfunction. According to recent studies, neurodegenerative diseases are associated with the accumulation of dysfunctional mitochondria. Selective autophagy of mitochondria, called mitophagy, can specifically degrade excess or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…It usually occurs in mitochondria that are defective after injury or stress. Mitophagy promotes the renewal of mitochondria and prevents the accumulation of dysfunctional mitochondria, which may lead to cellular degeneration ( Wang et al, 2022 ). Mitophagy is activated in mammalian cells by PINK1/Parkin-mediated mitophagy ( Iorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually occurs in mitochondria that are defective after injury or stress. Mitophagy promotes the renewal of mitochondria and prevents the accumulation of dysfunctional mitochondria, which may lead to cellular degeneration ( Wang et al, 2022 ). Mitophagy is activated in mammalian cells by PINK1/Parkin-mediated mitophagy ( Iorio et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…PINK1 affects the health of mitochondrial ( Nguyen et al, 2016 ). PINK1 activates Parkin via phosphorylation, which is an E3 ubiquitin ligase located in the cytoplasm ( Bingol and Sheng, 2016 ; Wang et al, 2022 ). YBX1, a positive regulator of mitophagy, by enhancing PINK1/PRKN-mediating mitophagy in brown adipocyte ( Wu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Saita et al found that depletion of Drp1, a protein involved in mitochondrial fission, led to decreased levels of MFNs and OPA1 [108]. The other studies highlight the significant linkage between parkin-dependent mitophagy and neurodegenerative diseases, including Alzheimer's and Parkinson's diseases [109][110][111].…”
Section: Protein Machinery In Mitochondrial Fusionmentioning
confidence: 93%
“…A significant topic implicated in the pathogenesis of NDDs is defective mitophagy [ 164 , 165 , 166 , 167 , 168 ]. It is defined as the selective autophagy or turnover of mitochondria.…”
Section: Biochemical Pathways Involving Protein Homeostasis Autophagy...mentioning
confidence: 99%